2015
DOI: 10.1177/1069072714565362
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Psychological Empowerment, Trust, and Iranian EFL Teachers’ Job Satisfaction

Abstract: This study aimed at relating trust and psychological empowerment to Iranian English as a foreign language (EFL) teachers’ job satisfaction. Participants were 217 (117 females and 100 males) Iranian EFL teachers teaching in secondary school. Four dimensions of psychological empowerment (meaning, competence, self-determination, and impact), three faculty trust (trust in principal, trust in colleague, and trust in students and parents), and two aspects of job satisfaction (intrinsic and extrinsic) were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 46 publications
3
43
0
13
Order By: Relevance
“…Hence, empowerment could be necessary among healthcare providers (Irvine et al, 1999). In spite of the importance of psychological empowerment to improve work outcomes (Ghani et al, 2009;Khany & Tazik, 2016;Saif & Saleh, 2013), few studies have investigated physiological empowerment with safety outcomes (Tong et al, 2015).…”
Section: Psychological Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, empowerment could be necessary among healthcare providers (Irvine et al, 1999). In spite of the importance of psychological empowerment to improve work outcomes (Ghani et al, 2009;Khany & Tazik, 2016;Saif & Saleh, 2013), few studies have investigated physiological empowerment with safety outcomes (Tong et al, 2015).…”
Section: Psychological Empowermentmentioning
confidence: 99%
“…Additionally, psychological empowerment affects job satisfaction (Khany & Tazik, 2016;Saif & Saleh, 2013), job performance (Indradevi, 2012), nursing practices environment (Wang & Liu, 2013), process engagement (Zhang & Bartol, 2010), quality of patient care (Bonias et al, 2010), workers' commitment (Malik et al, 2013), and perceived management commitment to quality (Howard & Foster, 1999). However, previous studies confirmed that there is a relation between quality and safety as work-related outcomes (Wanberg et al, 2013).…”
Section: Psychological Empowermentmentioning
confidence: 99%
“…Yra ir konkrečiai profesinei sričiai sukurtų darbuotojų psichologinio įga-linimo modelių. Irvine, Leatt, Evans ir Baker (1999) medicinos darbuotojų psichologinio įgalinimo modelį sudaro elgesio, verbalinis ir pasekmių dėmenys, o Kuokkanen, Leino-Kilpi ir Katajisto (2003) apibūdina psichologinį įgalinimą kaip asmeninio augimo ir tobulėjimo procesą Šių autorių metodu medicinos seserų įgalinimo raiška nustatoma pagal tai, kaip jos vertina savo charakteristikas, būdingas įgalintoms darbuotojoms, -moralinius principus, elgesio vientisumą (integralumą), profesionalumą, orientaciją į ateitį, socialumą (Kuokkanen & Leino-Kilpi, 2001;Kuokkanen, LeinoKilpi, & Katajisto, 2002;Istomina et al, 2012). Vyraujančių reiškinio koncepcijų apžvalga rodo, kad nėra vieno psichologinio įgalinimo modelio, tačiau įvairūs autoriai, nors ir nevienodais terminais, įvardija tas pačias esmines šio reiškinio sudedamąsias dalis: darbo prasmė darbuotojui, suvokta galimybė savarankiškai spręsti darbo klausimus (ir kartu -asmeninė atsakomybė už sprendimus) ir pasitikėjimas savo profesine kompetencija.…”
unclassified
“…Nustatytas platus padarinių spektras, pavyzdžiui, darbuotojų proakyvumas ir inovatyvus elgesys (Pieterse, Van Knippenberg, Schippers, & Stam, 2010;Arefin, Arif, & Raquib, 2015), kokybiškas klientų aptarnavimas (Barrutia, Charterina, & Gilsanz, 2009), geri darbo rezultatai ir kokybė (Li, Wei, Ren, & Di, 2015;Azeem, Abrar, Bashir, & Zubair, 2015), teigiamos nuostatos darbo, bendradarbių ir organi-zacijos atžvilgiu -pasitenkinimas darbu (Hechanova, Regina, Alampay, & Franco, 2006;Amundsen & Martinsen, 2015;Khany & Tazik, 2016), įsipareigojimas organizacijai (Fong & Snape, 2015;Jaiswal & Dhar, 2016;Chan, Nadler, & Hargis, 2015;Boonyarit, Chomphupart, & Arin, 2010), efektyvus komandų funkcionavimas ir rezultatai (Kirkman, Rosen, Tesluk, & Gibson, 2004;Voegtlin, Boehm, & Bruch, 2015).…”
unclassified
See 1 more Smart Citation